Pembinaan bangsa Malaysia [1]: Kajian empirikal tahap patriotisme belia - Syed Hussain, Tuan Pah Rokiah; Nasarah, Shamsul Anuar; Othman, Zaheruddin (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
A citizenry’s patriotism may be gauged from variables such as their knowledge of the nation’s administration system, pride in being citizens of the country, sense of belonging and loyalty to the country, upholding of the country’s good reputation through proper conduct, and willingness to enhance the country’s economic productivity. This study examined the patriotism level of Malaysian youths based on these indicators of patriotism.Primary data were gathered from a field survey of 1,500 randomly sampled Malaysian youths aged 15 to 30.Data analysis showed that the prevailing level of the youth patriotism was high at 73 percent with a mean of 7.26.Still, there was room for improvement and this could be found within the ambit of the country’s formal and informal education system designed to enhance all those patriotic values.